Immunodeficiency, Centromeric Instability, and Facial Dysmorphism (ICF) Syndrome: How HSCT alters the impairment of the DNA methylation process - Wojciech Homa; Joanna Wanat; Izabela Dzikowska; Agata Siejka; Daria Stefaniak; Aleksandra Warunek; Gabriela Gronowicz; Michał Chról; Weronika Zielińska (Journal of Education, Health and Sport)
Introduction and purpose In 2024, the EBMT Inborn Errors Working Party published a study that confirmed the beneficial role of hematopoietic stem cell transplantation (HSCT) in patients with immunodeficiency, centromeric instability, and facial dysmorphism (ICF) syndrome. In this article, we aim to present the characteristics of ICF in an accessible way, including its genetic background, clinical presentation, immunological alterations, and treatment options.